Case Report: Pansclerotic Morphea-Clinical Features, Differential Diagnoses and Modern Treatment Concepts - Ventéjou, Sarah; Schwieger-Briel, Agnes; Nicolai, Rebecca; Christen-Zaech, Stephanie; Schnider, Caroline; Hofer, Michael; Bogiatzi, Sofia; Hohl, Daniel; De Benedetti, Fabrizio; Morren, Marie-Anne (Frontiers in Immunology, 2021)
Pansclerotic morphea (PSM) is a rare skin disease characterized by progressive stiffening of the skin with or without the typical superficial skin changes usually seen in morphea (localized scleroderma). Standard therapy, consisting of a combination of systemic glucocorticoids and methotrexate or mycophenolate mofetil, does rarely stop disease progression, which may lead to severe cutaneous sclerosis and secondary contractures. Little is known about the efficacy of newer biologicals such as abatacept, a fusion protein antibody against CTLA-4, or tocilizumab, a fully humanized IL-6R antibody, in the treatment of this pathology. We present the case of an 8 year old girl with an unusual, progressive stiffening of the skin, which was eventually diagnosed as pansclerotic morphea. A treatment with systemic glucocorticoids and methotrexate combined with tocilizumab led to a good clinical response within 2 months after initiation. In this paper, we discuss differential diagnoses to be considered and this new promising treatment option based on a case review of the literature.